The above equation holds true for positive integers , , , and . Find .
Notation : denotes the Euler-Mascheroni constant .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First of all note the series ψ ( z + 1 ) + γ = k = 1 ∑ ∞ ( − 1 ) k + 1 ζ ( k + 1 ) z k For ∣ z ∣ < 1 Now multiplying both sides by z and then substituting z = − x we get − x ψ ( 1 − x ) − γ x = k ≥ 2 ∑ ζ ( k ) x k Now we see that ξ = k ≥ 2 ∑ k + 1 ζ ( k ) − 1 = k ≥ 2 ∑ ( ζ ( k ) − 1 ) ∫ 0 1 x k d x Interchanging summation and integration which can be justified by Tonelli's Theorem we get ∫ 0 1 ( ( k ≥ 2 ∑ ζ ( k ) x k ) − k ≥ 2 ∑ x k ) d x
Using the above obtained result alongwith the formula for infinite geometric progression we get ξ = ∫ 0 1 ( − x ψ ( 1 − x ) − γ x − 1 − x x 2 ) d x ξ = ∫ 0 1 ( − x ψ ( 1 − x ) − γ x − ( − x − 1 + 1 − x 1 ) ) d x
Now properly splitting the integrals we have ξ = ξ 1 + ξ 2
Where ξ 1 = − ∫ 0 1 ( x ψ ( 1 − x ) + 1 − x 1 ) And ξ 2 = ∫ 0 1 ( x + 1 − γ x ) d x = 2 3 − 2 γ
In ξ 1 we use the property that ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x to get ξ 1 = − ∫ 0 1 ( ( 1 − x ) ψ ( x ) + x 1 ) d x = − ∫ 0 1 ( ψ ( x ) + x 1 ) d x + ∫ 0 1 x ψ ( x ) d x
Now using the functional rule for digamma function that ψ ( z + 1 ) = ψ ( z ) + z 1 we get ξ 1 = − ∫ 0 1 ψ ( x + 1 ) d x + ∫ 0 1 x ψ ( x ) d x = [ ln ( Γ ( x + 1 ) ) ] 0 1 + ∫ 0 1 x ψ ( x ) d x = ∫ 0 1 x ψ ( x ) d x
So now ξ 1 = ∫ 0 1 x ψ ( x ) d x Now using IBP once we get ξ 1 = − ∫ 0 1 ln ( Γ ( x ) ) d x = − 2 1 ln ( 2 π ) Where I use the standard result ∫ 0 1 ln ( Γ ( x ) ) d x = 2 1 ln ( 2 π ) Which has been asked on Brilliant earlier also(I couldn't find the link to it).
So at the end we get ξ = ξ 1 + ξ 2 = 2 3 − 2 1 ln ( 2 π ) − 2 γ
Thus A + B + C + D = 8